Implementasi Pendekatan Komunikatif dalam Pembelajaran Bahasa Arab bagi Calon Jemaah Haji dan Umrah di Komunitas Tour and Travel The Park Mall : Implementation of the Communicative Approach in Teaching Arabic for Prospective Hajj and Umrah Pilgrims in the Tour and Travel Community at The Park Mall - Siti Alfi Aliyah; Susanti, Susanti; Rif’atul Fadhilah; Muh Fuad Achsan; Miftah Toriqul Ikhwani (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
The learning of Arabic for prospective Hajj and Umrah pilgrims is an essential necessity to facilitate smooth communication during their pilgrimage journey in the Holy Land. This study analyzes the implementation of a communicative approach in Arabic language learning conducted by the Arabic Language Education Study Program at Universitas Muhammadiyah Karanganyar within the Tour and Travel Community at The Park Mall. The program aims to equip pilgrims with practical and applicable language skills. This research employs a qualitative method with a case study approach, utilizing data collection techniques such as observation, interviews, documentation, and relevant literature review. A total of 21 participants took part in the Arabic language learning program, which applied a communicative approach through conversation simulations, role-playing, and context-based exercises related to worship and daily life in Mecca and Medina. The findings indicate that the implementation of a communicative approach has a positive impact on improving participants' Arabic language skills, providing them with a more practical understanding and speaking ability. Before joining the program, most participants struggled to comprehend and use Arabic. However, after engaging in communicative-based learning, they showed significant progress in speaking, understanding instructions, and recognizing basic Arabic writing commonly encountered during their pilgrimage journey.